Deconstructing the narrative of power: a critical discourse analysis of Tempo.Co ‘Bagi-bagi konsesi tambang’ in youtube. - Arzeti, Dinda Syakilla Dwi Putri; Elviria, Samia; Muhaimin, Muhaimin; Mairita, Desy; HM, Pahrudin; Maghfirah, Noor Khalida (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2025)
ABSTRACT This study examining the convergence of textual strategies, newsroom politics, algorithmic infrastructures, and investigates how investigative journalism functions in platformized media environments. The study examines Tempo.co's Bocor Alus Politik episode "Bagi-Bagi Konsesi Tambang" on YouTube using Fairclough's Critical Discourse Analysis (CDA) to learn how oppositional discourse is created, shared, and limited within a platform-driven ecosystem. In order to determine how investigative journalism manages the conflicts between democratic accountability and platform monetization logics, this study integrates algorithmic visibility, newsroom power dynamics, and digital news discourse—all of which were previously studied independently. The results show that Tempo deliberately uses linguistic framing, narrative sequencing, and visual cues to criticize elite networks related to the distribution of mining concessions in Indonesia. However, YouTube's recommendation system, which favors engagement-optimized content and has an impact on editorial choices, shapes these textual strategies. The study also demonstrates how the production and platforming of investigative pieces are heavily influenced by internal newsroom politics, including negotiations between editorial autonomy and commercial divisions. This study provides a cutting-edge framework that explains how investigative journalism becomes both a market-oriented adaptation to algorithmic economies and a form of political intervention by combining CDA with platform analysis and production studies. In addition to practical implications for media organizations trying to preserve critical independence while functioning within digital infrastructures that control visibility, revenue, and audience reception, the study provides theoretical insights into the hybrid nature of platformized watchdog journalism. ABSTRAK Dengan mengkaji konvergensi strategi tekstual, politik ruang redaksi, dan infrastruktur algoritmik, studi ini menyelidiki bagaimana jurnalisme investigasi berfungsi dalam lingkungan media berbasis platform. Studi ini mengkaji episode "Bagi-Bagi Konsesi Tambang" dari Tempo.co di YouTube menggunakan Analisis Wacana Kritis (CDA) Fairclough untuk mempelajari bagaimana wacana oposisional diciptakan, dibagikan, dan dibatasi dalam ekosistem berbasis platform. Untuk menentukan bagaimana jurnalisme investigasi mengelola konflik antara akuntabilitas demokratis dan logika monetisasi platform, studi ini mengintegrasikan visibilitas algoritmik, dinamika kekuatan ruang redaksi, dan wacana berita digital—yang semuanya telah dikaji secara independen sebelumnya. Hasil penelitian menunjukkan bahwa Tempo sengaja menggunakan pembingkaian linguistik, pengurutan naratif, dan isyarat visual untuk mengkritik jaringan elit terkait distribusi konsesi pertambangan di Indonesia. Namun, sistem rekomendasi YouTube, yang mengutamakan konten yang dioptimalkan untuk interaksi dan berdampak pada pilihan editorial, membentuk strategi tekstual ini. Studi ini juga menunjukkan bagaimana produksi dan platforming artikel investigasi sangat dipengaruhi oleh politik internal ruang redaksi, termasuk negosiasi antara otonomi editorial dan divisi komersial. Studi ini menyediakan kerangka kerja mutakhir yang menjelaskan bagaimana jurnalisme investigasi menjadi adaptasi berorientasi pasar terhadap ekonomi algoritmik sekaligus bentuk intervensi politik dengan menggabungkan CDA dengan analisis platform dan studi produksi. Selain implikasi praktis bagi organisasi media yang mencoba mempertahankan independensi kritis sambil berfungsi dalam infrastruktur digital yang mengendalikan visibilitas, pendapatan, dan penerimaan audiens, studi ini memberikan wawasan teoretis tentang sifat hibrida jurnalisme pengawas yang berbasis platform.